A cross of iron : Harry S. Truman and the origins of the national security state, 1945 - 1954 - Hogan, Michael J. 1943- (Cambridge Univ. Press, 1998)
In A Cross of Iron, one of the country's most distinguished diplomatic historians addresses the domestic underside of America's expanding global role in the first decade of the Cold War. The result is the fullest account yet of one of the most important developments in recent American history - the emergence of a national security state where none had existed before. Drawing on prodigious research in archival and manuscript materials, Michael J. Hogan traces the process of state making as it unfolded in efforts to unify the armed forces, organize the Defense Department, harness science to military purposes, mobilize military manpower, and distribute the cost of defense across the economy. In tracing these efforts, not to mention the great debates over defense spending and the scope of the country's commitments around the world, Hogan's challenging narrative brings into sharp focus the dramatic postwar transformation of the American state.